Antitumor effects of LPM5140276 and its potential combination with SHP2 inhibition in KRASG12D-mutant cancer - Hu, Zhengping; Zou, Fangxia; Zhao, Fengjuan; Yu, Pengfei; Zhu, Haibo; Yu, Liting; Wang, Wenyan; Ye, Liang (Frontiers in Pharmacology, 2026)
KRASG12D is a predominant mutation in pancreatic and colorectal cancers whose targeting has remained a therapeutic challenge. In this study, we introduced LPM5140276 as a potent KRASG12D inhibitor that forms a salt bridge with the Asp12 residue; furthermore, we evaluated its antitumor efficacy, action mechanism, and synergy with the SHP2 inhibitor RMC4550. LPM5140276 was observed to bind to GDP-loaded KRASG12D with high affinity, exhibiting a dissociation constant (KD) of 3.1 × 10−3 nM and an IC50 of 0.5 nM, which was superior to its binding to GTP-loaded KRASG12D. In KRASG12D-mutant cells, LPM5140276 significantly inhibited cell viability by suppressing ERK and AKT phosphorylation to induce G0/G1 cell-cycle arrest and promote apoptosis, which contributed to its antitumor effect in vivo. However, rebound phosphorylation of ERK/AKT and increased SHP2 phosphorylation following the treatment suggested the emergence of bypass resistance. Notably, the combination of LPM5140276 and RMC4550 synergistically suppressed ERK and SHP2 phosphorylation, enhanced G0/G1 arrest and apoptosis, and improved the antitumor efficacy. Thus, LPM5140276 is a promising KRASG12D inhibitor, whose combination with SHP2 inhibition represents a viable strategy for overcoming resistance.